PECAN: National Weather Service High Resolution Radiosonde Data. Version 1.0 - UCAR/NCAR - Earth Observing Laboratory (UCAR/NCAR - Earth Observing Laboratory, 2015)
The National Weather Service (NWS) routinely releases radiosondes at 00 and 12 UTC with occasional special releases at sites throughout the United States. This data set includes the quality controlled PECAN NWS soundings released at 22 sites throughout the Central Plains during the PECAN field phase (1 June to 16 July 2015). A total of 2055 quality-controlled, high vertical resolution (1-second) soundings are contained in the final PECAN data set.
Keywords: Upper Air; Sounding; Radiosondes; Balloons/Rockets > > RADIOSONDES > > 2516981b-e560-479d-ba96-f8edfb54efe9; Radiosondes; Earth Remote Sensing Instruments > Passive Remote Sensing > Profilers/Sounders > > RADIOSONDES > > c79ff20c-08c1-41f5-8f68-13c1b6d34ba8; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC TEMPERATURE > UPPER AIR TEMPERATURE > VERTICAL PROFILES; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WATER VAPOR > WATER VAPOR INDICATORS > HUMIDITY > RELATIVE HUMIDITY; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC TEMPERATURE > UPPER AIR TEMPERATURE; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > WIND PROFILES > WIND VELOCITY/SPEED PROFILES; EARTH SCIENCE > ATMOSPHERE > ALTITUDE > GEOPOTENTIAL HEIGHT; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WATER VAPOR > WATER VAPOR PROFILES; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > UPPER LEVEL WINDS > BOUNDARY LAYER WINDS; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > UPPER LEVEL WINDS > WIND SPEED; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > UPPER LEVEL WINDS > WIND DIRECTION; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC PRESSURE > ATMOSPHERIC PRESSURE MEASUREMENTS; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC TEMPERATURE > UPPER AIR TEMPERATURE > DEW POINT TEMPERATURE; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC TEMPERATURE > UPPER AIR TEMPERATURE > BOUNDARY LAYER TEMPERATURE; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > WIND PROFILES > WIND DIRECTION PROFILES; PECAN; Plains Elevated Convection at Night